The Role of Political and Servant Leadership on Public Transparency and Trust - Irman Puansah; Siti Mahmudah; Amândio de Araújo Sarmento; Fadhila Sidiq Permana; Gede Wirata (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Transparency and public trust have become essential pillars for strengthening governmental legitimacy, particularly in democratic systems facing rising complexity and declining citizen confidence. This study aims to examine how the integration of political leadership and servant leadership can enhance institutional transparency and reinforce public trust. Using a qualitative literature study, the research analyzes scholarly articles, policy reports, and empirical studies published within the last decade. Data were collected through document analysis and evaluated using qualitative content analysis to identify thematic patterns related to leadership, transparency, and trust-building mechanisms. The findings indicate that servant leadership contributes significantly to ethical governance, open communication, and participatory decision-making, thereby promoting a transparency-oriented organizational culture. Meanwhile, political leadership provides the structural authority and policy direction necessary to institutionalize transparency through formal mechanisms such as open-government initiatives and public accountability systems. The integration of these two leadership approaches produces a synergistic effect: ethical values embedded in servant leadership are strengthened by the institutional power of political leadership, resulting in more consistent transparency practices and stronger public trust. This study offers strategic implications for public-sector leaders seeking to improve institutional legitimacy, accountability, and citizen engagement.